The competencies of the shift leader in the intensive care unit setting, in a private hospital group in South Africa - Elzabé Nel; Ann Müller; Adele Colyn (AOSIS, 2011)
Newly qualified intensive care nurses are forced into positions of authority and responsibility as shift leaders at an early stage and are not given a chance to consolidate their new knowledge with practice. They have to be responsible and accountable not only for their own actions, but also for those of their staff. The purpose of this study was to explore and describe the competencies of the shift leader in the intensive care unit setting to determine whether there is a gap between what is expected of the shift leader and what is happening in reality. A quantitative, descriptive design was used and cluster sampling was implemented.Questionnaires were used to gather data from three clusters, comprising 11 hospitals from a single private hospital group. Of the 251 questionnaires that were handed out to intensive care personnel (including trained and non-trained staff), 98 were returned, resulting in a response rate of 39%. An in-depth literature study and submission of questionnaires to experts before being administered to respondents ensured validity and reliability. Results were used to describe a typology of the competencies of the shift leader in the intensive care setting and indicated that respondents classified competencies related to the application of the nursing process in the intensive care unit in all its facets as essential competencies. None were classified as a critical competency and only four were classified as specific competencies. All respondents in the three clusters regarded their shift leaders as competent. Opsomming Pas-gekwalifiseerde, intensiewesorg-verpleegkundiges word op 'n vroeë stadium as skofleiers in posisies van gesag en verantwoordelikheid geplaas en word nie die kans gegun om hul nuwe kennis met die praktyk te konsolideer nie. Tog moet hulle verantwoordelikheid en aanspreeklikheid aanvaar nie net vir hul eie aksies nie, maar ook vir dié van hul personeel. Die doel van hierdie studie was om die vaardighede van skofleiers in die opset van die intensiewesorg-eenheid te ondersoek en te beskryf om te bepaal of daar 'n gaping bestaan tussen wat van hulle verwag word en wat in werklikheid gebeur. 'n Kwantitatiewe, beskrywende ontwerp is gebruik en 'n trossteekproef is geïmplementeer. Vraelyste is gebruik om data in te samel van drie trosse bestaande uit 11 hospitale van 'n enkele privaathospitaalgroep. Van die 251 vraelyste wat uitgedeel is aan intensiewesorg-personeel (insluitend opgeleide en nie-opgeleide personeel), is 98 terugontvang, wat vertaal na 'n responskoers van 39%. 'n Diepgaande literatuurstudie en voorlegging van vraelyste aan deskundiges voordat dit aan respondente uitgedeel is, het bygedra tot geldigheid en betroubaarheid. Resultate is gebruik om 'n tipologie van die vaardighede van skofleiers in 'n intensiewesorg-eenheid te beskryf en dit het geblyk dat respondente die vaardighede wat verband hou met die verpleegproses in die intensiewesorg-eenheid in al sy fasette as noodsaaklike vaardighede klassifiseer. Geen vaardigheid is as kritiek geklassifiseer nie en slegs vier vaardighede is as spesifieke vaardighede geklassifiseer. Al die respondente in die drie trosse het hul skofleiers as vaardig beskou.